2021
DOI: 10.1007/s10648-021-09613-w
|View full text |Cite
|
Sign up to set email alerts
|

Spacing and Interleaving Effects Require Distinct Theoretical Bases: a Systematic Review Testing the Cognitive Load and Discriminative-Contrast Hypotheses

Abstract: Spaced and interleaved practices have been identified as effective learning strategies which sometimes are conflated as a single strategy and at other times treated as distinct. Learning sessions in which studying information or practicing problems are spaced in time with rest-from-deliberate-learning periods between sessions generally result in better learning outcomes than massed practice without rest-from-deliberate-learning periods. Interleaved practice also consists of spaced sessions, but by interleaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 128 publications
(71 reference statements)
0
22
0
2
Order By: Relevance
“…There are likely several reasons for the generally positive effects of recess and physical activity on children's academic performance (see Chen et al, 2021;Pellegrini & Bjorklund, 1997). For example, recess, or simply breaks between rigorous academic tasks, serves to distribute practice on a topic, which has repeatedly been shown to enhance learning (e.g., Chen et al, 2018).…”
Section: Increasing Opportunities For Physical Activitiesmentioning
confidence: 99%
“…There are likely several reasons for the generally positive effects of recess and physical activity on children's academic performance (see Chen et al, 2021;Pellegrini & Bjorklund, 1997). For example, recess, or simply breaks between rigorous academic tasks, serves to distribute practice on a topic, which has repeatedly been shown to enhance learning (e.g., Chen et al, 2018).…”
Section: Increasing Opportunities For Physical Activitiesmentioning
confidence: 99%
“…Während beim geblockten Lernen (blocked practice) Lerninhalte nacheinander thematisiert werden (aaabbbcccddd), werden diese beim verschachtelten Lernen (interleaved practice) abwechselnd behandelt (abcdabcdabcd). Das Verschachteln der Lerninhalte geht mit kognitiv anspruchsvollen Diskriminations-und Vergleichsprozessen einher, weshalb es auch als wünschenswerte Erschwernis beim Lernen (Bjork & Bjork, 2011;Carvalho & Goldstone, 2015;Chen et al, 2021;Dunlosky et al, 2013) und damit als Strategie zur kognitiven Aktivierung von Lernenden begriffen werden kann (Lipowsky et al, 2019). Durch die Diskriminations-und Vergleichsprozesse kann der Erwerb nicht nur prozeduralen, sondern auch konditionalen Wissens unterstützt werden (Birnbaum et al, 2013;Brunmair & Richter, 2019;Ziegler & Stern, 2014).…”
Section: Verschachteltes Lernen Zur Förderung Flexiblen Rechnensunclassified
“…Im Gegensatz zum geblockten Lernen (blocked practice), bei dem einzelne Lerninhalte eines Themengebiets nacheinander behandelt werden, werden diese beim verschachtelten Lernen durchmischt unterrichtet. Hierdurch können lernförderliche Diskriminationsprozesse ausgelöst werden, die die Lernenden dabei unterstützen, die zu lernenden Inhalte zu unterscheiden (Carvalho & Goldstone, 2015;Chen et al, 2021). Im Kontext von halbschriftlichen Subtraktionsstrategien und der schriftlichen Subtraktion konnten bisherige Ergebnisse des vorliegenden LIMIT-Projekts 1 zeigen, dass das verschachtelte Lernen die flexible, adaptive und korrekte Anwendung von Subtraktionsstrategien besser als ein geblocktes Vorgehen fördern kann (Nemeth et al, 2019(Nemeth et al, , 2021.…”
Section: Introductionunclassified
“…have provided a useful critique of Chen et al (2021) paper in which we suggested the possibility that resting from cognitive activity can allow working memory recovery and so provide an explanation of the spacing effect while the discriminative-contrast hypothesis can provide an explanation of the interleaving effect. Before addressing the specific criticisms of Sana et al, we would like to indicate the general goals of our 2021 paper.…”
Section: Introductionmentioning
confidence: 99%